2004
DOI: 10.1007/s10310-003-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Light availability and understory vegetation four years after thinning in a Larix leptolepis plantation of central Korea

Abstract: We measured photosynthetically active radiation (PAR) beneath the forest canopy, understory species' richness and diversity, and biomass in a Larix leptolepis plantation in central Korea 4 years after thinning. Four different thinning intensities (control, 10%, 20%, and 40% stocking reduction) were applied in 1997. Mean annual intercepted PAR at 30 cm and 1 m above ground level was significantly different among the thinning intensities and strongly correlated with the number of stems remaining after thinning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
2
23
2
1
Order By: Relevance
“…This indicates that in the studied plantations more light reaching under the canopies does not result higher diversity of species. This result is not in agreement with the findings of Son et al (2004), who reported an increase in the diversity of species with an increase, in the light in a Larix leptolepis plantation. This difference could be attributed because of differences in plantation species, micro-environments under the studied plantations, availability of seed sources, type of regenerated species (shade lover or not).…”
Section: Effects Of Light and Density Of Plantation Trees On The Undecontrasting
confidence: 99%
See 1 more Smart Citation
“…This indicates that in the studied plantations more light reaching under the canopies does not result higher diversity of species. This result is not in agreement with the findings of Son et al (2004), who reported an increase in the diversity of species with an increase, in the light in a Larix leptolepis plantation. This difference could be attributed because of differences in plantation species, micro-environments under the studied plantations, availability of seed sources, type of regenerated species (shade lover or not).…”
Section: Effects Of Light and Density Of Plantation Trees On The Undecontrasting
confidence: 99%
“…This result is not consistent with Son et al (2004), who showed that more light in the understory vegetation encouraged understory plant production. This difference could be resulted because of differences in the studied plantations and type of regenerated species.…”
Section: Effects Of Light and Density Of Plantation Trees On The Undecontrasting
confidence: 93%
“…However, the ideal methods of forest management including thinning should consider increasing whole biodiversity (Hartley 2002). Especially, new thinning strategies must take into account further knowledge concerning the effects of thinning procedures on structural diversity and spatial variation of understory vegetation (Ares et al 2010) as understory vegetation acts as a major contributor to species diversity in ecosystems, and is influenced by the overstory plants (Son et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thinning with the stem-only harvesting introduces a significant volume of leaves and twigs to the forest floor as thinning residues (Hytö-nen & Moilanen 2014). The increase in light availability following thinning could also promote litter production from understory vegetation (Son et al 2004). Thus, it can be speculated that the non-significant effect of thinning on the forest floor C storage in the present study may be due to the fact that the influences of thinning cancel each other out, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%